Assessing The Effectiveness Of Employee Motivational Strategies: A Case Study Of Offinso College Of Education - Adjei, Augustine; Nkansah, Irene (International Journal of Scientific Research and Management (IJSRM), 2021)
Teachers in Ghana have expressed a lot of dissatisfaction about the lack of human resource development, poor working conditions, poor remuneration and poor human relations. There are motivational strategies that motivate employees and improve their effectiveness. These motivational strategies, even though are in place, have had little impact on employees. This study was therefore carried out to identify the motivational strategies that are implemented in the Ghana Education Service with emphasis on Offinso College of Education [OCE] and their effectiveness towards performance. The researcher adopted purposive sampling to gather data from the administrative heads, convenient sampling technique for tutors as well as simple random sampling to gather data from nonteaching staff. The descriptive study design was adopted for the study with the case study approach been used. A sample size of one hundred and ten (110). The mixed study approach was used thus both qualitative and qualitative data were gathered from both primary and secondary sources of information. Questionnaires, focus group discussion as well as interview were the instruments used in the data gathering process. Descriptive statistics was used to analyze the data with the aid of the Statistical Package for Social Scientist (SPSS) which was presented with tables, frequencies and percentages and mean. The study found job security and job flexibility, opportunity for advancement and promotional opportunities were somehow strong motivational packages that exist in the college while communication gap, the lack of being duly recognized, lack of accommodation, job interference, and poor remuneration were some motivational challenges employees face that affect their effectiveness. The study therefore recommends the deepening and institution of more intrinsic and extrinsic motivational packages to enhance their effectiveness.